Investigation of the effects of radial clearance on the screw conveyor performances for different inclinations - Bolat, Berna; Temiztas, Birgul Ascioglu; Sezer, Enes (ELSEVIER SCIENCE INC, 2024)
Screw conveyors are widely used for bulk material transportation. This study investigates the critical role of radial clearance, the gap between the screw and the conveyor body, on performance across various inclination angles. The Discrete Element Method (DEM) is employed to analyze the effects of different radial clearances on conveyor performance for concrete aggregate and sand as bulk materials. Volumetric efficiencies and capacity losses serve as key performance indicators, quantitatively assessed for each radial clearance and inclination combination. Experimental validation is conducted to corroborate the findings. In the study, the optimal radial clearance was identified as 1.5 to 3 times of the particle size. This optimal clearance minimizes the material jamming and increases the performance for screw conveyors with different inclinations and bulk material types as a result. (c) 2024 Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences. Published by Elsevier B.V. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Screw conveyors; Radial clearance; Discrete element method (DEM); Volumetric efficiency; Conveyor performance; Engineering; Materials Science